Synthesis and structure of tricarbonyl(η6-arene)chromium complexes of phenyl and benzyl D-glycopyranosides - Ziegler, Thomas; Heber, Ulrich (Beilstein Journal of Organic Chemistry, 2012)
A series of 15 glycoside-derived tricarbonyl(η6-arene)chromium complexes were prepared in 19–87% yield by heating fully acetylated or methylated aryl O-, S-, N- and C-glycosides of D-glucopyranose and D-mannopyranose with hexacarbonylchromium. All tricarbonylchromium complexes were fully characterized. The structures of nine crystalline complexes were determined by X-ray diffraction, revealing unusual intra- and intermolecular nonclassical hydrogen bonds.
Keywords: aryl glycosides; carbohydrates; transition-metal complex; tricarbonyl(arene)chromium